IKEA in Indonesia: The Synergy of Swedish Public Diplomacy and Nation Branding - Anggia Valerisha; Raden Fahrizal Ahadisuryo (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2020)
Public diplomacy and nation-branding are two popular concepts and closely related to diplomacy activities by both state and non-state actors. Szondi discusses the possible inter-connections of the two concepts and formulates understanding on how his concept can help to explain the various attempts of both state and non-state actors in achieving national interest. The unit analysis of this study is Sweden as state actor and IKEA as multi-national corporation. The existence of IKEA as company with its global-popular brand has becoming concerns for further research particularly on how IKEA brand as the instrument to supports Sweden’s public diplomacy. This study aims to analyze Swedish public diplomacy and nation-branding in Indonesia through the IKEA brand as the case study and by using the model of public diplomacy and nation-branding proposed by Szondi. The study uses qualitative method with data collection carried out through documentation studies from 2014-2018. The findings indicate that the IKEA brand has unique characteristics. In Szondi’s model, IKEA brand positioned in the incision between the area of public diplomacy activities and the area of nation-branding, which is described by Szondi as the fourth model. Through the IKEA brand, there is a synergy between Swedish public diplomacy activities and its nation- branding strategy. The IKEA brand has succeeded not only in the promotion of its products or companies, but also contributed to a positive image and reputation of Sweden and, increase social and economic engagement with Indonesia.